2015
DOI: 10.1021/acs.jpcb.5b09656
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxidation/Reduction in Water and Protein: Studies with DFTB3/MM and VALBOND Molecular Dynamics Simulations

Abstract: We apply two recently developed computational methods, DFTB3 and VALBOND, to study copper oxidation/reduction processes in solution and protein. The properties of interest include the coordination structure of copper in different oxidation states in water or in a protein (plastocyanin) active site, the reduction potential of the copper ion in different environments, and the environmental response to copper oxidation. The DFTB3/MM and VALBOND simulation results are compared to DFT/MM simulations and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 132 publications
1
33
0
Order By: Relevance
“…In this state, the protein has a rich spectroscopy, and has been studied by several different spectroscopic techniques including electronic absorption, circular dichroism, magnetic circular dichroism, and x‐ray absorption spectroscopies . Alongside these experimental measurements there have been numerous theoretical studies with a wide variety of different levels of approximation . These studies have led to an understanding of the nature of the observed spectroscopic features and detailed insight into the electronic structure of the active site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this state, the protein has a rich spectroscopy, and has been studied by several different spectroscopic techniques including electronic absorption, circular dichroism, magnetic circular dichroism, and x‐ray absorption spectroscopies . Alongside these experimental measurements there have been numerous theoretical studies with a wide variety of different levels of approximation . These studies have led to an understanding of the nature of the observed spectroscopic features and detailed insight into the electronic structure of the active site.…”
Section: Introductionmentioning
confidence: 99%
“…Deeth studied the oxidized form of a range of blue copper proteins, including plastocyanin, with ligand field molecular mechanics (LFMM) and found an entatic strain energy of about 10 kcal mol −1 . Further hybrid quantum mechanics/molecular mechanics (QM/MM) approaches and implicit models of the protein environment have been used to obtain optimized geometries of each state.…”
Section: Introductionmentioning
confidence: 99%
“…Both processes can be cast within the framework of MS-ARMD 67,234 but alternative techniques have also been employed. Typical applications are the investigation of the change in the solvent structure around metal-complexes [235][236][237][238][239] or the spectroscopic signatures accompanying proton transfer, 68,69,[240][241][242][243][244][245] or the energetics of proton transfer in proteins. 246 A field by itself is the investigation of proton transfer in bulk water for which a myriad of FF-based techniques have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive description of the method can be found in the literature . It has been found that this method is successful for predicting the binding structure of biomolecule complexes involving weak interaction systems and has already been used to study the binding of biomolecules . In this work, we used the conjugate gradient algorithm for the structure optimizations, with the force convergence criterion set at 10 −4 au and the charge convergence criterion set to 10 −4 electrons.…”
Section: Models and Methodsmentioning
confidence: 99%